Chelation Therapy with Oral Solution of Deferiprone in Transfusional Iron-Overloaded Children with Hemoglobinopathies - Alexandros Makis; Nikolaos Chaliasos; Sapfo Alfantaki; Paraskevi Karagouni; Antigone Siamopoulou (Anemia)
Iron overload in hemoglobinopathies is secondary to blood transfusions, chronic hemolysis, and increased iron absorption and leads to tissue injury requiring the early use of chelating agents. The available agents are parenteral deferoxamine and oral deferiprone and deferasirox. There are limited data on the safety and efficacy of deferiprone at a very young age. The aim of our study was the presentation of data regarding the use of oral solution of deferiprone in 9 children (mean age 6.5, range 2–10) with transfusion dependent hemoglobinopathies (6 beta thalassemia major, 1 thalassemia intermedia, and 2 sickle cell beta thalassemia). The mean duration of treatment was 21.5 months (range 15–31). All children received the oral solution without any problems of compliance. Adverse reactions were temporary abdominal discomfort and diarrhea (1 child), mild neutropenia (1 child) that resolved with no need of discontinuation of treatment, and transient arthralgia (1 child) that resolved spontaneously. The mean ferritin levels were significantly reduced at the end of 12 months (initial 2440 versus final 1420 μg/L, ). This small study shows that oral solution of deferiprone was well tolerated by young children and its use was not associated with major safety concerns. Furthermore, it was effective in decreasing serum ferritin.